HISTORICAL STUDY OF SEMANTICS IN ARABIC LINGUISTICS AND ITS RELEVANCE TO ARABIC LANGUAGE EDUCATION - Nurfadilah Nurfadilah; Danny Azhar; Agustiar Agustiar (Lingeduca: Journal of Language and Education Studies, 2026)
Historical semantic study in Arabic linguistics is a field that traces the journey of Arabic word meanings across time. This study aims to examine the development of historical semantics in the Arabic linguistic tradition diachronically, from the classical period to the contemporary era, while analyzing its relevance to Arabic language education practices in Indonesia. Using a qualitative descriptive approach based on library research, data were collected from primary and secondary sources including classical Arabic linguistic works, recent scientific journals, and Arabic language education curriculum documents. The findings indicate that Arabic historical semantics has undergone rich dynamics, from the classical Arabic lexicographic tradition (8th century CE) to its integration with 20th-century Western modern linguistics. Furthermore, a thorough understanding of Arabic lexical meaning shifts proves pedagogically relevant, particularly in developing competence in reading classical texts, enriching vocabulary instruction, and enhancing comprehension of religious discourse. This study concludes that integrating the historical-semantic dimension into Arabic language learning in Indonesia is not merely an added value, but an epistemological necessity that has long been underrecognized in national curriculum design.